The foundation and building blocks of inclusive and equitable classrooms in STEM - Hubenig, Katelynn (Kansas State University, 2023)
Equity and Inclusion are matters of Justice, a laudable goal in its own right. They are further matters of Justice in science, technology, engineering, and mathematics (STEM) classrooms. There have been calls across the globe for more diversity in the workforce. Specifically in Canada and the United States of America, there is a need for diverse problem solvers to tackle the unique challenges societies face today. STEM disciplines provide individuals with the skills to help solve these problems, but are also disciplines that push out individuals from underrepresented groups, and therefore lack diversity. We see a great attrition of qualified individuals and diversity at the university level that perpetuates the lack of diversity in the workforce. One research area of discipline-based education research (DBER) assesses how equitable and inclusive classrooms can support and retain individuals from underrepresented groups in their fields. While the evidence of how to use equitable and inclusive classroom practices and tools is vast, these practices and tools are not fully accepted by the wider teaching community at the university level. We discuss what equity and inclusion are, the current state of STEM disciplines and the (lack of) progress toward equity and inclusion and the effect of retention of individuals from underrepresented groups. We provide a discussion on two main teaching practices in STEM classrooms, traditional lecturing and active learning, and where these practices uplift or fail students, especially those underrepresented in their discipline. These discussions aim to help the reader start their journey toward a better understanding of equity and inclusion in STEM classrooms.
Keywords: Equity and inclusion in STEM